Naive Bayes Algorithm for Sentiment Analysis on Spider-Man Movie: No Way Home: Data Mining - Makarim, Ziddan; Nawangsih, Ismasari; Sanudin, Sanudin (Information Technology and Science (ITScience), 2024)
The rapid development of streaming platforms has significantly changed the landscape of movie consumption. The ease of access and social interaction in online communities has led to the creation of a new pop culture around movies. One interesting phenomenon is the movie Spider-Man: No Way Home, which sparked heated and viral conversations on various social media platforms. This research aims to analyze audience sentiment towards the movie Spider-Man: No Way Home using Naïve Bayes algorithm. Review data collected from online platforms was processed to identify positive and negative sentiments. The choice of Naïve Bayes algorithm is based on its efficiency and ability to classify text. The results showed that the model built was able to classify sentiment with an accuracy of 72.34%. The model is more effective in identifying positive reviews than negative, indicating a positive response from the majority of viewers. However, the model still needs to improve its performance in classifying negative sentiments. This research makes an important contribution in understanding audience preferences and evaluating the success of a movie, especially in the context of the digital era. The results can be utilized by the film industry to improve production quality, marketing strategies, and content development that is more relevant to audience preferences. In addition, this research also opens up opportunities for further development, such as the use of more complex algorithms or combining with other sentiment analysis techniques, as well as application to various types of social media content.